Real Time Vehicle Recognition System for Secure Environment - Rai, Amrita; Agrawal, Reshu; Karatangi, Shylaja V.; nayak, Seema (Journal of physics. Conference series, 2021)
An automatic system based on “Digital Image Processing” technology is developed using MATLAB tool to recognize the vehicle by identifying the license plate. A database is linked to the MATLAB processor, which takes input as the detected number plate. Information about the owner is extracted and electronic format of the challan is generated if the number plate is in wrong format. Also in case of theft or crime, the required number plate is fed to the database system and if it is matched with the detected number plate, an alert is generated. The captured image is in RGB format which is converted into grey scale. Here theories and techniques used to identify the area and Edge detector operators is used to measure threshold values to get the dilated image. After that flood fill operation can be used to stuff the wholes to get a fine binary picture. The fundamental steps to identify the vehicle license plate and plate size, then the partitioned picture is amplified with gray scale only to get the license plate of vehicle. Afterwards the template matching process done to match the image from license plate and template’s picture, thus the number plate detected is then matched with one stored in the database system to get complete information of the vehicle owner. The first section in your paper.